Scratched From Memory: The 1986 Prison Massacres and the Limits of Acceptable Memory Discourse in Post-conflict Peru. Issue 2 (2nd April 2020) - Willis, Daniel
Abstract : In this article, I seek to demonstrate how the 1986 massacre of nearly 250 inmates at El Frontón and Lurigancho prisons can shed light on the political and social exclusion faced by Shining Path militants, during and since Peru's internal armed conflict (1980–2000). I will analyse how Peruvian prisons have been historically used as sites of exclusion for political opponents of the Peruvian state. Then, through an analysis of literary responses to the massacres and the wider conflict, I will demonstrate how cultural producers have sought to recover Shining Path memories of violence, in order to highlight both the persistent socioeconomic conditions that precipitated Shining Path's insurrection and the continuing impunity for perpetrators of state violence. Finally, I will show that the recuperation of Shining Path memories in literary sources is undermined by the continuing silence of El Frontón in Lima's memoryscape, and say what this tells us about the limits of acceptable memory discourse in present day Peru.